Simultaneous determination of tocopherols and tocotrienols in hazelnuts by a normal phase liquid chromatographic method. - Amaral, Joana S. (2008)
A normal-phase high-performance liquid chromatography (NP-HPLC) method for the determination of tocopherols and tocotrienols in hazelnuts is reported. Three extraction procedures (with and without saponification) were assayed, being the best results obtained with a simple solid-liquid extraction procedure. Chromatographic separation was achieved using an Inertsil 5 SI column using isocratic elution with n-hexane/1,4-dioxane (95.5:4.5, v/v) at a flow rate of 0.7 mL/min. The effluent was monitored by a series arrangement of a diode-array followed by a fluorescence detector. All compounds were separated in a short period of time (17 min). The method proved to be rapid, sensitive, reproducible and accurate, allowing the simultaneous determination of all vitamin E isomers.